Production and characterization of bacteriocin produced by lactic acid bacteria isolated from rusip - Arifah Kusumarwati; Ninoek Indriati; Irma Hermana (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
Research was conducted to produce and characterize bacteriocin produced by lactic acid bacteria (LAB) isolated from rusip, a traditional Bangkanese fermented fish product. Experiment was started by isolation of lactic acid bacteria from rusip, followed by screening to obtain the best isolate which has the highest bacterial inhibition activity. The selected isolate was then identified and used to produce crude bacteriocin. The crude bacteriocin was characterized through its stability in high temperature and proteolytic enzymes, inhibitory spectrum, pH sensitivity and effect of surfactants. The result showed that CN1.10a isolate which was identified as Lactococcus lactis subsp lactis has the highest bacterial inhibition activities; therefore it was selected to produce crude bacteriocin. The bacteriocin produced was heat stable, sensitive to proteolytic enzymes i.e. proteinase-K and papain but not to RNase. It inhibited Escherichia coli, Listeria monocytogenes and Lactobacillus plantarum. It stable at pH 2.0 to 6.0. Among surfactans used sodium dodecyl sulphate (SDS), lauryl sarcosine and EDTA were able to stimulate bacteriocin production, while the production were strongly inhibited by Tween 20, Tween 80, Triton X-100 and urea. Based on the above characteristic, the bacteriocin was suitable to be used as a preservative of food which has to be processed at high temperature.